Graphene as a nanofiller for enhancing the tribological properties and thermal conductivity of base grease. Issue 72 (20th December 2019) - Fu, Hui; Yan, Guoping; Li, Meng; Wang, Hao; Chen, Yapeng; Yan, Chao; Lin, Cheng-Te; Jiang, Nan; Yu, Jinhong
Abstract : The addition of graphene-reinforced grease to the mechanical friction surface can effectively reduce the friction coefficient and accelerate heat transportation. Abstract : During mechanical processes, violent friction and wear between the friction contact surfaces not only causes wear to mechanical components, reducing the instrument life, but also causes friction heat, reducing the working efficiency of machines during operation. The addition of graphene-reinforced grease to the mechanical friction surface can effectively reduce the friction coefficient and improve the thermal conductivity. In this work, the tribological properties and thermal conductivity of base grease with graphene were investigated systematically. The tribological results showed that the grease with 2 wt% graphene had the best tribological properties among all these greases. The wear scar diameter and average friction coefficient of graphene grease with 2 wt% graphene reached 0.43 mm and 0.10 (the values for base grease are 0.50 mm and 0.118), respectively. In addition, the average friction coefficient and wear scar diameter increased proportionally with the increasing load and frequency. The thermal conductivity of the grease with 4 wt% graphene reached 0.28 W (m K) −1, an increase of 55.5% in comparison with the base grease. It is proposed that the addition of graphene into the base grease effectively enhanced the tribological properties and thermal conductivity.